Effect of multiple micronutrient supplements v. iron and folic acid supplements on neonatal mortality: a reanalysis by iron dose. Issue 8 (25th August 2022) - Gomes, Filomena; Agustina, Rina; Black, Robert E; Christian, Parul; Dewey, Kathryn G; Kraemer, Klaus; Shankar, Anuraj H; Smith, Emily; Tumilowicz, Alison; Bourassa, Megan W
Abstract: Objective: Antenatal multiple micronutrient supplements (MMS) are a cost-effective intervention to reduce adverse pregnancy and birth outcomes. However, the current WHO recommendation on the use of antenatal MMS is conditional, partly due to concerns about the effect on neonatal mortality in a subgroup of studies comparing MMS with iron and folic acid (IFA) supplements containing 60 mg of Fe. We aimed to assess the effect of MMS v . IFA on neonatal mortality stratified by Fe dose in each supplement. Methods: We updated the neonatal mortality analysis of the 2020 WHO guidelines using the generic inverse variance method and applied the random effects model to calculate the effect estimates of MMS v . IFA on neonatal mortality in subgroups of trials ( n 13) providing the same or different amounts of Fe, that is, MMS with 60 mg of Fe v . IFA with 60 mg of Fe; MMS with 30 mg of Fe v . IFA with 30 mg of Fe; MMS with 30 mg of Fe v . IFA with 60 mg of Fe; and MMS with 20 mg of Fe v . IFA with 60 mg of Fe. Results: There were no statistically significant differences in neonatal mortality between MMS and IFA within any of the subgroups of trials. Analysis of MMS with 30 mg v . IFA with 60 mg of Fe (7 trials, 14 114 participants), yielded a non-significant risk ratio of 1·12 (95 % CI 0·83 to 1·50). Conclusion: Neonatal mortality did not differ between MMS and IFA regardless of Fe dose in either supplement.